THE EFFECT OF TEACHING CULTURAL CONTENT ON INTERMEDIATE EFL LEARNERS’ READING COMPREHENSION ABILITY - Razavi, Masoumeh; Gilakjani, Abbas Pourhosein (TEFLIN Journal, 2020)
This study investigated the effect of teaching cultural content on Iranian intermediate English as a foreign language (EFL) learners’ reading comprehension. To this end, 60 intermediate EFL learners from Shokouh Institute in Motelqu, Mazandaran, Iran were selected randomly and assigned to two groups, namely the control group and experimental group; 30 participants in each group were chosen based on their performance using the Oxford Placement Test (OPT). This study used a quasi-experimental, pretest-posttest control group research design. After the OPT, the reading comprehension pre-test was given to the participants to check their initial reading comprehension. During a six-week treatment period, both control and experimental groups received the same routine lesson plan of the institute but only the experimental group enjoyed the culture instruction in order to test its effect on learners’ reading comprehension improvement. At the final stage, the post-test was given to check their reading comprehension after the six-week treatment period. The data were analyzed using an Independent Samples T-test and a series of paired Samples T-tests. The results of this study showed that receiving cultural content instruction improved learners’ reading comprehension. In general, the results of experimental group supported the effect of teaching cultural content on Iranian learners’ reading comprehension.